Mitogen-activated protein kinase phosphatase 1 controls broad spectrum disease resistance in Arabidopsis thaliana through diverse mechanisms of immune activation - Berlanga, Diego José; Molina, Antonio; Torres, Miguel Ángel (Frontiers in Plant Science, 2024)
Arabidopsis thaliana MITOGEN-ACTIVATED PROTEIN KINASE PHOSPHATASE 1 (MKP1) negatively balances production of reactive oxygen species (ROS) triggered by Microbe-Associated Molecular Patterns (MAMPs) through uncharacterized mechanisms. Accordingly, ROS production is enhanced in mkp1 mutant after MAMP treatment. Moreover, mkp1 plants show a constitutive activation of immune responses and enhanced disease resistance to pathogens with distinct colonization styles, like the bacterium Pseudomonas syringae pv. tomato DC3000, the oomycete Hyaloperonospora arabidopsidis Noco2 and the necrotrophic fungus Plectosphaerella cucumerina BMM. The molecular basis of this ROS production and broad-spectrum disease resistance controlled by MKP1 have not been determined. Here, we show that the enhanced ROS production in mkp1 is not due to a direct interaction of MKP1 with the NADPH oxidase RBOHD, nor is it the result of the catalytic activity of MKP1 on RBHOD phosphorylation sites targeted by BOTRYTIS INDUCED KINASE 1 (BIK1) protein, a positive regulator of RBOHD-dependent ROS production. The analysis of bik1 mkp1 double mutant phenotypes suggested that MKP1 and BIK1 targets are different. Additionally, we showed that phosphorylation residues stabilizing MKP1 are essential for its functionality in immunity. To further decipher the molecular basis of disease resistance responses controlled by MKP1, we generated combinatory lines of mkp1-1 with plants impaired in defensive pathways required for disease resistance to pathogen: cyp79B2 cyp79B3 double mutant defective in synthesis of tryptophan-derived metabolites, NahG transgenic plant that does not accumulate salicylic acid, aba1-6 mutant impaired in abscisic acid (ABA) biosynthesis, and abi1 abi2 hab1 triple mutant impaired in proteins described as ROS sensors and that is hypersensitive to ABA. The analysis of these lines revealed that the enhanced resistance displayed by mkp1-1 is altered in distinct mutant combinations: mkp1-1 cyp79B2 cyp79B3 fully blocked mkp1-1 resistance to P. cucumerina, whereas mkp1-1 NahG displays partial susceptibility to H. arabidopsidis, and mkp1-1 NahG, mkp1-1 aba1-6 and mkp1-1 cyp79B2 cyp79B3 showed compromised resistance to P. syringae. These results suggest that MKP1 is a component of immune responses that does not directly interact with RBOHD but rather regulates the status of distinct defensive pathways required for disease resistance to pathogens with different lifestyles.